2020
DOI: 10.3390/ijms21031074
|View full text |Cite
|
Sign up to set email alerts
|

An Isolated Complex V Inefficiency and Dysregulated Mitochondrial Function in Immortalized Lymphocytes from ME/CFS Patients

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is an enigmatic condition characterized by exacerbation of symptoms after exertion (post-exertional malaise or “PEM”), and by fatigue whose severity and associated requirement for rest are excessive and disproportionate to the fatigue-inducing activity. There is no definitive molecular marker or known underlying pathological mechanism for the condition. Increasing evidence for aberrant energy metabolism suggests a role for mitochondrial dysfunction in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
74
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 67 publications
(127 reference statements)
17
74
3
2
Order By: Relevance
“…As a consequence, the gender proportions in the total cohort also differed significantly (p = 0.002) between the patient and control groups used for the lymphocyte death rates. Nevertheless, this additional cohort allowed us to verify our previous finding [32], that the lymphocyte death rates in culture were not age-or gender-dependent, and to confirm published reports that lymphocyte viability is stable for long periods in frozen storage [33,43].…”
Section: Participant Cohortsupporting
confidence: 82%
See 4 more Smart Citations
“…As a consequence, the gender proportions in the total cohort also differed significantly (p = 0.002) between the patient and control groups used for the lymphocyte death rates. Nevertheless, this additional cohort allowed us to verify our previous finding [32], that the lymphocyte death rates in culture were not age-or gender-dependent, and to confirm published reports that lymphocyte viability is stable for long periods in frozen storage [33,43].…”
Section: Participant Cohortsupporting
confidence: 82%
“…We reported, in an accompanying paper, that after recovery from frozen storage, PBMCs from ME/CFS patients die markedly faster in culture than those from healthy controls [32]. A time course revealed that the percentage of dead cells, and the difference between patients and controls, increased dramatically from 24 to 72 h of culture.…”
Section: Me/cfs and Patient Blood Samples Can Be Distinguished By Thementioning
confidence: 92%
See 3 more Smart Citations